Metode Demonstrasi Pada Materi Shalat Dalam Pelajaran Fikih Di Madrasah Ibtidaiyah - Ananda, Fauzi; Tanjung, Rahmad Mulyadin; Celine, Devi Rofidah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Fikih (Islamic jurisprudence) education at the Madrasah Ibtidaiyah (Islamic elementary school) level plays a vital role in shaping students’ understanding and practice of worship from an early age. One of the most essential topics in Fikih lessons is the practice of prayer (shalat), which must be mastered not only theoretically but also through proper practical execution. However, in reality, many students face difficulties in understanding the procedures of shalat when it is taught merely through verbal explanation or rote memorization. This issue highlights the need for a more concrete and applicable teaching approach. This study aims to describe and analyze the implementation of the demonstration method in teaching shalat material within Fikih subjects at Madrasah Ibtidaiyah Humayroh. The research uses a qualitative approach with a phenomenological method. Data were collected through observations, interviews with teachers, the principal, and students, as well as document analysis. Data analysis followed the interactive model of Miles and Huberman, with triangulation and member checking to ensure data validity. The findings indicate that the demonstration method effectively enhances students’ understanding and practical skills in performing shalat. Teachers played an active role in modeling and guiding students, while students showed high enthusiasm and engagement throughout the learning process. This study implies that the demonstration method is highly effective for teaching worship practices that emphasize psychomotor and religious values. Furthermore, the findings affirm the importance of contextual and experiential learning approaches in cultivating students’ religious character from an early age.